Literature Review : The Effect Of Diabetes Self Management Education On Self- Efficacy In Diabetes Mellitus Patients - Desak Putu Fahmi Octaviyanti (Politeknik Kesehatan Kartini Bali, 2020)
Diabetes Mellitus is a long-term or chronic disease with an increasing prevalence, knowledge about the disease is lacking and people cannot manage the disease. One way to be able to prevent complications from diabetes apart from pharmacological therapy can be by providing education in the form of diabetes self management education. diabetes self management education can be done to increase knowledge and self efficacy in people with diabetes mellitus. From this literature review to identify, examine, and explain information about the effect of diabetes self management education on self efficacy in patients with diabetes mellitus. This literature review uses databases such as Google Scholar, EBSCO, DOAJ, Research Gate and Microsoft Academic with the keywords diabetes self management education, self efficacy, and published diabetes mellitus based on inclusion and exclusion criteria. From the 4 articles and 7 journals obtained, 8 of them showed the results that diabetes self management education was effective against self efficacy in patients with diabetes mellitus. Diabetes self management education can be used as an intervention in terms of education in patients with diabetes mellitus to increase knowledge and self efficacy.